Preferences for accessing sexual and reproductive health information and services among adolescent girls and young women in higher learning institutions in Tanzania: A qualitative study - Lusajo Jason Mwalukunga; Fabiola Vincent Moshi; Stephen Matthew Kibusi (PLoS ONE, 2026)
Introduction Adolescence is a critical developmental stage characterized by significant physical, emotional, and cognitive changes, including sexual maturation. However, this population group faces challenges such as early sexual initiation, limited contraceptive access, high sexually transmitted infection risks, including HIV (with 43% of new HIV infections in Tanzania occurring among youth, with higher rates found among young women), and unintended pregnancies, negative outcomes of limited access to sexual and reproductive health (SRH) information and services. Social, cultural, and policy constraints restrict access to SRH services, highlighting the need to understand adolescents’ preferences to improve accessibility and health outcomes. Aim The study aimed to explore the preferences for accessing sexual and reproductive health information and services among adolescent girls and young women (AGYW) in higher learning institutions in Tanzania. Methods This qualitative descriptive study was conducted at two universities in Dodoma, Tanzania. Purposive sampling recruited 13 sexually active students aged 19–24. Data were collected through in-depth interviews conducted in Swahili, audio-recorded, and transcribed verbatim. Data saturation was reached at the 13th interview. Results Young women reported different preferences for accessing sexual and reproductive health (SRH) information and services. They accessed SRH information through community, media, and healthcare-based sources. Family members,(particularly sisters)and friends, were key information sources, though parental reluctance limited access. Social media and search engines provided privacy but raised concerns about misinformation. Healthcare facilities were perceived as reliable yet unwelcoming, leading many participants to prefer over-the-counter services. Participants advocated for reliable online platforms to enhance the accessibility and accuracy of SRH information. Conclusion This study highlights AGYW’s preferences for accessing SRH information, emphasizing digital platforms and peer education. Strengthening these approaches while improving the youth-friendliness of healthcare settings is essential for improving SRH outcomes among this population.